PENERAPAN ALGORITMA K-MEANS UNTUK ANALISIS NILAI TAHFIDZ SANTRI BERDASARKAN NILAI FASHOHAH DAN TAJWID (STUDI KASUS : PESANTREN MODERN AT-TAQWA BOGOR) - Najib, Muhammad Alfin; Rasiban (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Modern Islamic boarding schools, like other Islamic boarding schools, are part of Islamic education in Indonesia. The purpose of this research is to develop a system that uses the K-Means Clustering method to analyze the tahfidz values ​​of students based on fashohah and tajwid values. This system utilizes the RapidMiner Application as a testing tool. This research has several important contributions. First, by applying the K-Means Clustering method, the system can group students based on similar tahfidz abilities. This can help educators (Tendik) Modern Islamic Boarding School At-Taqwa Gunungputri Bogor in monitoring and evaluating the progress of students in memorizing the Qur'an. With this research, the Leaders of the At-Taqwa Modern Islamic Boarding School hope that the New Santri Acceptance Committee (PSB) and especially the Educators of the At-Taqwa Modern Islamic Boarding School can be useful and assist them in determining the value of Tahfidz and can improve the quality of the Tahfidz Program at this Islamic Boarding School